More Than This : Poems - Kirby, David, 1944- (Book collections on Project MUSE., 2019)
"In More Than This, David Kirby transports readers to a place of grave observations and warnings, a place of darkness yet also, on occasion, of relief. "You can't save everyone," he writes in "Just Behind the Fence, a Train"--"You save whom you can." Inflected with his trademark humor and observation, the poems in More Than This are consoling, eye-opening, and deeply moving"--